Implementasi Blended Service pada Layanan Sirkulasi Era Pandemi Covid-19 di UIN SAIZU Purwokerto - Nisa-un Naja (UIN Mataram, 2021)
The COVID-19 pandemic, which continues to spread to various countries, has had a huge impact on many sectors. The education sector is one of the most affected by the COVID-19 virus. Learning that was originally able to be done face-to-face must be changed to distance learning or online. Being one of the sources of reference in a learning and information center, the library must innovate in providing services so that it can still meet the needs of users. This study discusses the application of mixed services to circulation services at the UIN SAIZU Purwokerto library during the pandemic. This study uses a qualitative descriptive method with interviews and observations as a deepening of data collection. The borrowing service uses a drive thru system, while the return service is carried out via expedition or if you are still in one city you can leave the book to the security guard in a neat package and give the user's name, number, and cellphone number. Based on the results of the study, it was shown that the application of blended services in the circulation service of the UIN SAIZU Purwokerto Library, although it encountered several obstacles, could be implemented well.